DETERMINAN AKUNTANSI RUMAH TANGGA - Hartinah, Siti; Lestari, Rindu Ferdina; Triwarti, Hairul; Bahiroh, Eloh (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to analyze the influence of financial literacy and financial behavior on the implementation of household accounting among housewives in the South Larangan area of Tangerang City. The research design used an associative quantitative approach. Primary data were collected through questionnaires from 35 housewives selected through random sampling. Data analysis was performed using multiple linear regression using SPSS, preceded by validity, reliability, and classical assumption tests (normality, heteroscedasticity, multicollinearity).The results indicate that financial literacy and financial behavior positively and significantly influence the implementation of household accounting. Good financial literacy improves housewives' ability to manage finances, while disciplined financial behavior (budgeting, control, and saving) directly contributes to the effectiveness of accounting practices. These findings support the Theory of Planned Behavior, indicating that positive attitudes and perceived behavioral control, driven by financial literacy and behavior, shape effective household accounting intentions and actions. Contribution to practice/policy: Beneficial for housewives and assists families in systematic financial management. This research focuses only on housewives in the Larangan Selatan and does not cover a wider area. Keywords : Accounting, household, Financial Literacy and Financial Behavior